Sosialisai dan Pelatihan Pembuatan Eco-Enzym Dari Sampah Organik Rumah Tangga Desa Cangkuang - Irawati, Irawati; Aditya, Muhammad Yanuar; Zulfaqor, Muhammad Rafhi; Basyir, Luthfi Mochammad; Aulia, Azra Nadhira; Ningrum, Tania; Fujiawati, Azqia Nurul; Al chabibah, Fahima 'Alimatush Sholichah; Sagita, Lisa; Pertama, Adinda Puteri; Ghazali, Muhammad Ridwan (Yayasan Cendekia Gagayunan Indonesia, 2025)
Eco-enzyme from household organic waste. The socialization and training activities were carried out in Cangkuang Village, Leles District, Garut Regency on September 5, 2024, involving 36 mothers from the Family Welfare Empowerment. The implementation method of this program consists of two main stages of delivering theoretical material about Eco-Enzyme and a practical demonstration of its manufacture. The material from this socialization includes an explanation of Eco-Enzyme, the fermentation process, and its benefits for the environment and daily life. The demonstration includes the stages of making Eco-Enzyme from start to finish, including collecting organic materials, mixing in the right ratio, and storage techniques. Participants showed high enthusiasm, with 20 residents willing to practice making Eco-Enzyme after the socialization and 5 residents actively asking questions. This program succeeded in providing theoretical understanding and practical skills to participants, encouraging sustainable organic waste management and the use of environmentally friendly products in everyday life.